Development and Evaluation of Dipyridamole Multi Unit Floating Mini-Tablets - Rama Koteswararao Kotharapu; Srinivas lankalapalli (Journal of Global Pharma Technology, 2019)
The objective of the present work was to formulate and to characterize multi unit floating drug delivery system of Dipyridamole to increase the bioavailability and sustain the drug release properties up to 8 h with more predictable drug release kinetics that avoids all or nothing emptying effect. Dipyridamole floating mini-tablets were prepared by effervescent approach with melt granulation and direct compression techniques alone and in combination using Hydroxypropyl methylcellulose (HPMC) K100M and Compritol 888 ATO at different concentrations (20%, 30% and 40% w/w) alone and in combination. Evaluations were carried out on physical parameters, floating behavior and influence of type of polymer on drug release rate of prepared mini tablet formulations. All the formulations were subjected to various quality control and in-vitro dissolution studies and corresponding dissolution data were fitted to popular release kinetic equations in order to evaluate release mechanisms and kinetics. All the dipyridamole floating mini tablet formulations followed zero order kinetics. As per Korsmeyer-Peppas equation, the release exponent “n” ranged 0.619-0.748 indicating that drug release from all the formulations was by non-Fickian diffusion mechanism. Based on the results, dipyridamole floating mini tablets prepared by employing combination of 15% w/w HPMC K100M and 15% w/w Compritol 888 ATO offered desired in-vitro floating time and drug dissolution profile.